From Stages to Process: Fowler and Jones’s Analysis of Faith Development in Madrasah Ibtidaiyah Children - Rofi'ah, Siti; Inayati, Isna Nurul (Journal Of Islamic Education And Pesantren, 2026)
This article aims to analyze the faith development of Madrasah Ibtidaiyah (MI) children through the perspectives of James W. Fowler and Benjamin Jones. The study is motivated by the tendency of religious learning in MI to remain normative, transmissive, and memorization-oriented, which limits children’s religious experience and reflection. This research employs a qualitative approach using library research. Data were drawn from Fowler’s major work on Stages of Faith, Jones’s article on the reconstruction of faith development through a process-based framework, and supporting literature on developmental psychology and Islamic education. The data were analyzed through a conceptual-comparative approach by comparing Fowler’s stage-based model and Jones’s process-based model. The novelty of this article lies in integrating Fowler’s stage theory and Jones’s process-based approach to examine MI children’s faith development within Islamic religious learning. The findings show that MI children are generally situated within the intuitive–projective and mythic–literal stages, marked by concrete, symbolic, narrative, and literal understandings of religion. Jones’s perspective further indicates that children’s faith develops through religious socialisation and early questioning. The synthesis affirms that children’s faith development involves both developmental structure and meaning construction. This study implies the need for Islamic religious learning in MI to be more contextual, dialogical, reflective, and experience-based.